Mekanisme Pemberian Izin Usaha Pariwisata Pada Usaha Solus Per Aqua (SPA) di Kawasan Sanur - I Made Dwi Bimantara; I Nyoman Putu Budiartha; Ida Ayu Putu Widiati (Jurnal Analogi Hukum, 2022)
The proliferation of spa businesses in the Sanur area is expected to bring a positive competitive atmosphere among entrepreneurs to improve the quality of the services they provide. However, in practice, several spa businesses in the Sanur area do not have a tourism business registration permit. The purpose of this study is to find out (1) the implementation of a tourism business license on a spa business in the Sanur area; (2) the constraints and efforts of the Denpasar City Government in implementing tourism business permits for spa businesses in the Sanur area. The type of research used is a statutory approach and a fact approach. The results of the study show that (1) the SPA business license as an applicant must first complete the conditions that have been determined by the relevant Office, then after the conditions are valid, a review will be carried out directly at the location and then the permit is issued by the Investment Office. and Denpasar City One Stop Services on behalf of the Mayor; and (2) the legal basis for granting SPA business permits in Denpasar City Regulation No. 13 of 2015 concerning tourism business registration, the government and related agencies seek to optimize business actors to register their businesses in order to have legal certainty that is the guide in running the business. , but in the community there is a lack of information about the importance of permits in the operation of SPA businesses in the Sanur area.